Fueling Financial Sustainability in Emerging Markets: An Investigation of ESG Public Policy and Other Determinants in the Oil and Gas Industry through Effective Financial Planning - Aizada, Zhakupova; Saule, Arystanbayeva; Parida, Issakhova; Aliya, Shakbutova; Faizulayev, Alimshan (International Journal of Energy Economics and Policy, 2023)
This article’s major goal is to pinpoint the variables that affect the capital structure and financial viability of the oil and gas sector in the regions that make up the Eurasian Economic Union. Data on oil and gas businesses in the Eurasian Union from 2012 to 2020 were gathered using the Orbis Database. All currently operating businesses with recent financial data were painstakingly obtained. 2,757 businesses with pertinent financial data in total were gathered. It includes a broad variety of oil and gas firms that have so far been the subject of inquiry. The results show that firm-specific factors are very important in determining the financial viability of oil and gas enterprises in the EUEA regions. For instance, both size and tax policy matter in driving the financial sustainability and leverage of companies. Furthermore, in contrast to CAPSTR, the oil price has had an enormous positive impact on the financial sustainability of oil and gas companies in EAEU regions. The results illustrate that ESG factors substantially affect financial sustainability in a negative way. The results show that oil and gas businesses use cutting-edge, environmentally friendly technologies in accordance with ESG Public Policy. Managers should continue to improve their strategies based on the growth of their businesses by utilizing new cutting-edge environmentally friendly technologies that will be suitable for stringent ESG Public Policy regulations. Overall results indicate that managers and practitioners should work on new strategies for expansion and penetration into the new markets in the EUEA regions.